2018
DOI: 10.17984/adyuebd.447349
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Grade 5th Turkish Textbook in terms of Picture-Text Relationship

Abstract: Textbooks are one of the tools that contribute to the learning and training of learners. Textbooks with an easy-to-access guide should be prepared in a way that fits student-level and supports student development in terms of form and content. Textbooks designed in accordance with the level of the students are also attracted by students. The preparation of these books by taking into consideration the qualifications required for the tools used in education helps to achieve the educational objectives. One of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
2
0
4
Order By: Relevance
“…According to the findings, the illustrations in the Turkish textbook were found to be inadequate in terms of helping children to develop creative imagination, individuals with a great imagination and artistic taste, and in terms of developing children's imagination. Demirel, Kökçü and Akbaba (2018) in their research in the 5th grade Turkish textbook aims to reveal the relationship between the pictures and texts. In the eight texts examined, it was seen that the pictures in combination with the text were selected according to the content of the texts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the findings, the illustrations in the Turkish textbook were found to be inadequate in terms of helping children to develop creative imagination, individuals with a great imagination and artistic taste, and in terms of developing children's imagination. Demirel, Kökçü and Akbaba (2018) in their research in the 5th grade Turkish textbook aims to reveal the relationship between the pictures and texts. In the eight texts examined, it was seen that the pictures in combination with the text were selected according to the content of the texts.…”
Section: Resultsmentioning
confidence: 99%
“…Bu bağlamda bakıldığında bile çocuk kitaplarındaki resimlerin çocuğa göre olmasının önemi daha iyi anlaşılabilir." (Özer, 2007, s. 431 (Baş ve İnan Yıldız, 2014;Çakır, 2013;Demirel, Kökçü ve Akbaba, 2018;İşcan ve Cımbız, 2018;Sever, 2013).…”
Section: Introductionunclassified
“…Resimlerin kitabın veya metinlerin başlığıyla uyumlu olması çocuğun anlam kurma sürecini hızlandırması açısından önemlidir. (Demirel, Kökçü & Akbaba, 2018) Resimli çocuk kitapları çocuğun bilişsel gelişimi başta olmak üzere hem bakış açısı hem hayal dünyasını şekillendirmesi hem dil gelişiminde farkındalık kazanması açısından çocuk edebiyatında önemli bir yer tutmaktadır (Fang, 1996). Çocuklar, resimler aracılığıyla dünyayı tanırken aynı zamanda metinleri okuyarak kelime haznesini geliştirir.…”
Section: Maddeunclassified
“…According to these results, it can be stated that the Iranian book is designed a little better than the Turkey book in terms of page design. Demirel, Kökçü, and Akbaba (2018) found that the pictures were on the same page with the texts in the 5th grade Turkish textbook, which they examined in terms of the picture-text relationship. However, Akın (2015) revealed in his research that there is not enough visuality in the grammar studies included in the Turkish workbooks, and therefore, visual elements are not sufficiently utilized in grammar teaching.…”
Section: Extended Abstractmentioning
confidence: 99%